2010
DOI: 10.1097/pai.0b013e3181bdf4e7
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Thyroid Transcription Factor-1 Expression by 2 Monoclonal Antibodies in Pulmonary and Nonpulmonary Primary Tumors

Abstract: Thyroid transcription factor-1 (TTF-1) is a transcription factor that plays a role in the development and physiology of the thyroid and lungs. Expression of TTF-1 is used as a marker of lung and thyroid clinically. Commercially available clones of TTF-1 monoclonal antibodies, 8G7G3/1 and SPT24, have been reported to have different sensitivities for the detection of neoplasms of different origins. Although they are used extensively in daily practice, a comprehensive comparative study of these antibodies in a wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
114
4
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(126 citation statements)
references
References 28 publications
7
114
4
1
Order By: Relevance
“…16,17,29 The reason for this reactivity is most likely the use of a lower-specificity TTF-1 antibody (SPT24; NovoCastra) in this study, whereas it was previously shown that a higher-specificity (but lower sensitivity) TTF-1 clone 8G7G3/1 (DAKO) is consistently non-reactive in squamous cell carcinomas positive by SPT24. 30 All squamous cell carcinomas with TTF-1 reactivity in this study were negative for a novel adenocarcinoma marker Napsin A (data not shown) further supporting that this labeling is likely non-specific and is unrelated to glandular differentiation. Although this is a theoretical pitfall for classification of double-positive tumors as adenocarcinoma in laboratories utilizing SPT24 antibody, this is readily resolved by taking into account the ratio of TTF-1/p63 reactivity (low in squamous cell carcinoma vs high in adenocarcinoma) or p63/CK5/6 coexpression in squamous cell carcinoma.…”
Section: Discussionmentioning
confidence: 55%
“…16,17,29 The reason for this reactivity is most likely the use of a lower-specificity TTF-1 antibody (SPT24; NovoCastra) in this study, whereas it was previously shown that a higher-specificity (but lower sensitivity) TTF-1 clone 8G7G3/1 (DAKO) is consistently non-reactive in squamous cell carcinomas positive by SPT24. 30 All squamous cell carcinomas with TTF-1 reactivity in this study were negative for a novel adenocarcinoma marker Napsin A (data not shown) further supporting that this labeling is likely non-specific and is unrelated to glandular differentiation. Although this is a theoretical pitfall for classification of double-positive tumors as adenocarcinoma in laboratories utilizing SPT24 antibody, this is readily resolved by taking into account the ratio of TTF-1/p63 reactivity (low in squamous cell carcinoma vs high in adenocarcinoma) or p63/CK5/6 coexpression in squamous cell carcinoma.…”
Section: Discussionmentioning
confidence: 55%
“…In the past, numerous studies have focused on how to separate pulmonary from non-pulmonary neuroendocrine carcinomas, especially those of gastrointestinal or pancreatic origin using immunohistochemical markers. 7,[14][15][16][17][18][19][20][21][22][23] In this scenario, the use of TTF-1 has attracted a lot of attention. TTF-1 is a transcription factor that has been linked with expression in lung and thyroid neoplasms.…”
Section: Discussionmentioning
confidence: 99%
“…7,[24][25][26] The documented expression of TTF-1 in typical and atypical carcinoids of lung origin has been very variable ranging from 0 to 94% and 0 to 100%, respectively. 7,[14][15][16][17][18][19][20][21][22][23][27][28][29][30][31] This corresponds to an average expression rate of 34.3% for carcinoid tumors and 37.3% for atypical carcinoid tumors. This contrasts with neuroendocrine carcinomas of non-pulmonary origin, the majority which are reportedly negative for this marker, 15,16,18,19,23 although isolated cases of low grade gastrointestinal neuroendocrine carcinoma may show some reactivity with TTF-1.…”
Section: Discussionmentioning
confidence: 99%
“…This is an especially important consideration in small specimens, where internal control cells may not be represented and, unlike whole tissue sections, technical failure may not be apparent. Furthermore, it is well documented that TTF-1 (specifically the SPT24 clone) can rarely show focal reactivity in squamous cell carcinomas, 51 further complicating the dependence of p63 interpretation on TTF-1 status. p40 therefore offers a significant advantage over p63 in that its interpretation does not require CK5/6 as additional squamous marker and does not depend on TTF-1.…”
Section: P40 (Dnp63) In Pulmonary Squamous Cell Carcinomamentioning
confidence: 99%